Dampak dan Strategi Layanan Kesehatan Ibu Hamil Selama Pandemi COVID-19 - Nur Khotimah Elfiyani; Hadi Pratomo; Evi Martha; Prima Sesari Saraswati (JURNAL KESEHATAN REPRODUKSI, 2022)
Background: COVID-19 pandemic has both directly and indirectly affected the provision of the maternal health services. Stress caused by the pandemic also affecting the maternal health service.Objective: This research aimed to assess both the impact on the maternal health services and strategy performed to respond to the COVID-19 pandemic by the District Health Office (DHO) of South Tangerang.Method: The main method of this research is quantitative, then the quantitative findings are described qualitatively. The research team employed an in-depth interview via Zoom application (video teleconference) with 3 informants from the DHO. Meanwhile, the quantitative data were derived from dashboard of maternal health data K1, K4 and PF.  Qualitative data are analyzed using theme analysis which is adapted to the findings from those quantitative data.Results and Discussion: The impact of the maternal health service showed a significant decrease against maternal health service in April in which the loss percentage of coverage K1 = 32.93%; coverage K4= 26.43%; Childbirth by health professionals in health facility = 19.4%.Conclusion: The decreasing of maternal health services potentially increase complication to pregnant women and mother and child’s mortality rate. The DHO is suggested to continue improving strategies and efforts to maintain the access of maternal health services during the COVID-19 pandemic.